The Influence of Brand Image, Brand Loyalty and Word of Mouth (WOM) on Purchase Intention for Brand Somethinc - Nabila Wika Alya Fauzia; Albari (PT SOLUSI EDUKASI BERDIKARI, 2024)
This research aims to determine the influence of brand image, brand loyalty and word of mouth (WOM) on purchase intention for the Somethinc Brand. The growth of products related to skin care continues to increase. One of the local skincare brands that was founded in 2019 is Somethincnc. This research used a sample of 200 respondents from all over Indonesia. The sampling used was a non-probability sampling method using a purposive sampling technique. Meanwhile, the analysis technique in this research uses structural equation modeling (SEM) with using the AMOS version 24 program. The results there is a positive and significant influence between the variables brand image and brand loyalty, brand loyalty with WOM, and brand loyalty with purchase. intention. Meanwhile, there is an insignificant influence on the brand image variable with WOM and brand image and WOM with purchase intention.